The Status of Creativity Education in Intended Curriculum at Iranian Primary Schools: Current Situation and Prospective - Ahmad Rajabi Baghdar; Behrooz Mahram; Hossein Kareshki; Morteza Karami (مطالعات روانشناسی تربیتی, 2015)
With regards to the importance of creativity during the primary school, and with regards to the theories of affective and emotional development, the present study investigated the current status and future perspectives of intended curriculum in educational system of Iranian primary schools.  We explored the direct and indirect upstream documents related to creativity.  The study method was based on comparative and content analysis. Context unit and recording unit content were used to excavate upstream documents through comprehensive, total population sampling.  To identify the upstream documents, we sought experts' opinion from university professors and experienced research staff of Iranian Ministry of Education.  The results of scrutinizing the upstream documents indicated    propotion of the only a littel documents were related to the issue of creativity at primary schools.  To conclud, with the national curriculum having the least propotion.